2011
DOI: 10.1002/eji.201041235
|View full text |Cite
|
Sign up to set email alerts
|

Combination of lentivector immunization and low‐dose chemotherapy or PD‐1/PD‐L1 blocking primes self‐reactive T cells and induces anti‐tumor immunity

Abstract: In the last two decades, anti-cancer vaccines have yielded disappointing clinical results despite the fact that high numbers of self/tumor-specific T cells can be elicited in immunized patients. Understanding the reasons behind this lack of efficacy is critical in order to design better treatment regimes. Recombinant lentivectors (rLVs) have been successfully used to induce antigen-specific T cells to foreign or mutated tumor antigens. Here, we show that rLV expressing a murine nonmutated self/tumor antigen ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 57 publications
2
51
0
Order By: Relevance
“…37,38). Similar results may be obtained when radiotherapy is combined with blockade of other coinhibitory molecules, such as Tim-3, PD-1, or BTLA (39)(40)(41). A recent study has shown that anti-PD-1 antibody produced objective responses, 1 in 4 to 1 in 5 patients with advanced nonsmall cell lung cancer, melanoma, or renal-cell cancer (42).…”
Section: Discussionmentioning
confidence: 65%
“…37,38). Similar results may be obtained when radiotherapy is combined with blockade of other coinhibitory molecules, such as Tim-3, PD-1, or BTLA (39)(40)(41). A recent study has shown that anti-PD-1 antibody produced objective responses, 1 in 4 to 1 in 5 patients with advanced nonsmall cell lung cancer, melanoma, or renal-cell cancer (42).…”
Section: Discussionmentioning
confidence: 65%
“…In preclinical models, immunotherapy approaches that should lead to upregulation of PD-1 following activation of the immune system, such as recombinant cytokines or stimulatory antibodies or transfer of activated adoptive T cells, synergized with blockade of the PD-1-PD-L1 pathway (21,25,50).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades, anticancer vaccines have generally yielded disappointing clinical results [12]; however, increased understanding of the immune system, tumour immunology and vaccine technologies have allowed for the development of novel vaccine approaches that may be more efficacious. Against this background, sipuleucel-T became the first therapeutic cancer vaccine to receive Food and Drug Administration approval in the USA based on the prolongation of overall survival (OS) among men with metastatic CRPC, and the results from clinical trials with PROSTVAC®-VF, a poxvirusbased vaccine, have also been encouraging, thus providing proofof-principle for vaccines as a therapeutic approach [13][14][15].…”
Section: Vaccinesmentioning
confidence: 99%